Facile One-Step Hydrothermal Synthesis of Na3V2(PO4)2F3@C/CNTs Tetragonal Micro-Particles as High Performance Cathode Material for Na-Ion Batteries - Guo, Hao; Hu, Yong; Zhang, Xiaoping; Zhang, Rongliang; Hou, Dong; Sui, Yulei; Wu, Ling (Frontiers in Chemistry, 2019)
In this paper, we report a facile one-step hydrothermal method to synthesize tetragonal Na3V2(PO4)2F3@C particles which are connected by carbon nanotubes (CNTs) networks, using water as hydrothermal solvents. In this strategy, the reduction and crystallization of materials are carried out in the hydrothermal process (180 °C, 12 h), no additional heat treatment is required. The well-crystallized Na3V2(PO4)2F3 tetragonal grains (5-10 μm) are coated with amorphous nano-carbon and connected by highly conductive CNTs. The addition of CNTs can not only improve the conductivity of materials but also effectively inhibit the Na3V2(PO4)2F3 grains over growth. The Na3V2(PO4)2F3@C/CNTs composite possesses very flat charge/discharge platforms of 3.6 and 4.1 V. The sample exhibits an initial discharge specific capacity of 120.2 and 74.3 mAh g-1 at 0.1 C and 10 C rate, respectively, and shows excellent cyclical stability. The composite owns excellent electrochemical performances owing to the three-dimensional highly conductive network which is co-constructed by the CNTs and nano-carbon coating layer.